FACTORS AFFECTING THE PERCEPTION OF INDIVIDUAL TAXPAYERS TOWARD TAX FRAUD - Adwimurti, Yudhistira; Selfiani; Usmar; Prihanto, Hendi (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine factors such as tax information systems, work culture, and apparatus behavior that influence individual taxpayer perceptions of tax evasion. The research data was obtained from a questionnaire (primary) which was distributed to taxpayers who were at KPP Pratama Jakarta Kebayoran Baru Dua using the Simple Random Sampling method. Data processing used the SPSS version 23 program, while the analytical method used was descriptive statistics, data quality test, classic assumption test, model suitability test, multiple regression and hypothesis testing using the t test. Where the results of this study indicate that information technology has a positive and significant effect on tax fraud, work culture has a positive and significant effect on tax fraud, as well as employee ethics has a positive and significant effect on tax fraud. The results of the f test simultaneously explain that information technology, work culture, and employee ethics have a positive and significant effect on tax fraud.